Blood Plasma-Based Macroporous Scaffolds as Biocompatible Coatings to Restore Full-Thickness Excision Wounds - Tykhvynska, Olena A.; Rogulska, Olena Yu.; Volkova, Nataliya O.; Grischuk, Viktor P.; Revenko, Olena B.; Mazur, Svitlana P.; Lozinsky, Volodymyr I.; Petrenko, Yuriy O.; Petrenko, Oleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 044–048